The role of Emergency Response Team in university in meeting the emergency situation vis-a-vis the Malaysian mechanism of disaster management: University Malaysia Perlis (UniMAP) perspective - Azuddin, Bahari, Lt Kol (B); Evawaynie Valquis, Md. Isa; Faridah, Wahab (National Institute of Occupational Safety and Health (NIOSH), 2008)
Organized by National Institute of Occupational Safety and Health (NIOSH), 20th - 22nd August 2007 at Genting International Convention Centre (GICC), Genting Highlands, Malaysia.